Kinetics of niobium carbide reinforced composite coating produced in situ. (September 2015) - Cai, Xiaolong; Xu, Yunhua; Zhong, Lisheng; Zhao, Nana; Yan, Yinglin
Abstract: Niobium carbide (NbC) coatings on gray cast iron (Fe) (HT300) substrate were prepared by in situ synthesis at 1070, 1100, or 1130 °C for 15, 30, 45, or 60 min. The microstructure, elemental distributions, and phases of the coatings were characterized by scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectrometry, and X-ray diffraction. The kinetics of NbC coating growth by in situ synthesis was examined by measuring the depth of the NbC layer as a function of time and temperature. The results showed that the surface coating consists of NbC and α-Fe phases. The average grain size of NbC on the top surface of the coating was approximately 400 nm. The estimated growth rate constant varied from1.84 × 10 −9 cm 2 /s to2.57 × 10 −9 cm 2 /s, and activation energy of the NbC layer was calculated as 86.01 kJ/mol. Highlights: NbC coating on iron substrate was obtained by in situ method. The coating consists of α-Fe and NbC with the size of about 400 nm in substrate. The morphological and formation kinetics of the coating were investigated. Activation energy ( Q ) of the layer was calculated as 86.01 kJ/mol.